Hemovigilance: An analysis of adverse effects of blood donation among blood donors in a tertiary-care center - Anila Mani (Global Journal of Transfusion Medicine, 2021)
Background and Objectives: Hemovigilance is defined as a set of surveillance procedures covering the whole transfusion chain that is intended to collect and assess information on unexpected or undesirable effects resulting from the therapeutic use of labile blood products and to prevent future occurrence and recurrence. The primary goal of the study was to reduce the incidence of adverse events among blood donors and to make blood donation a pleasant experience. Prevention of adverse reactions at the time of blood donation is an important aspect of blood donor motivation and blood donor retention for future blood donations. Methods: This is a one and half year's prospective study which was conducted by the department of Transfusion Medicine. The study assessed untoward blood donor reactions, as a measure to further maximize the elimination of untoward reactions encountered during or after blood donation to secure a healthy donation-transfusion chain. We analysed the causative factors that can lead to complications in blood donors at different phases of blood donation like pre-donation, during donation and post donation phases. Results: Out of 8180 whole blood collections, 252 blood donor complications were observed during the study period. Out of this, 8.73% (n=22) adverse reactions were observed during donation at blood centre, while 91.27% (n=230) reactions occurred in blood donation camps. Among the camp donations, 61.30% (n=141) were at outdoor camps and 38.70% (n=89) were inside Blood Mobile. We had 83.23% (n=6808) of male blood donors and 16.77% (n=1372) of female donors. Out of the 66 females who developed complications, majority were belonging to the age group of 18-25 years. We had 37.90% (n=3100) first time donors and 62.10% (n=5080) repeat donors. Among the repeat donors, 34.59% (n=1757) were regular repeat donors and 65.41% (n=3323) were irregular repeat donors. Out of 130 first time donors who developed complications, 91.5% (n=119) were systemic reactions. 57.1% (n=12) of regular repeat donors and 80.2% (n=81) of irregular repeat donors developed systemic complications. Conclusion: Hemovigilance reporting has reinforced our blood donor safety as well as transfusion safety. Regular reporting of the adverse donor complications helped us to improve proper documentation of all aspects of a complete blood donation sequence not only by the medical officers but also by the blood centre staff members.